World War II behind closed doors Stalin, the Nazis and the West - Rees, Laurence 1957- (Pantheon Books, 2008)
Drawing on material available only since opening of archives in Eastern Europe and Russia, Rees reexamines the key choices made by Stalin, Churchill and Roosevelt during the war.--From publisher description